Ball Balancing - Abu-Abiah, Iman; Khalili, Aya (My University, 2018)
This project aims to balance a ball on a plate by keeping it on the surface and preventing falling. The most challenges that we faced how to balance the ball and how to sense the ball position in an accurate way and how to design an actuation mechanism for the project. To solve these challenges, first we need to know the Coordinates of the ball on the plate and then try to calculate the PID in order to know what are the angles that should the surface moved to balance the ball. The project will use python language and OpenCV on the Raspberry PI3 with its camera to do image processing and detect the location of the ball and then calculate the PID to send the angles to Arduino to move the servomotors by using serial port communication between Raspberry PI and Arduino inorder to set the ball in desired position.Chapter 1: Introductio